Septic arthritis caused by Salmonella sp - Wirawan Hambali; Sumariyono Sumariyono; K Chen (Indonesian Rheumatology Association, 2009)
Septic arthritis is a rare joint disorder, and can be caused by various pathogenic microorganisms, including bacteria, virus, mycobacterium, and fungus. The incidence of this infection is between 2 to 10 cases per 100,000 populations annually andcan reach as high as 30 to 70 cases per 100,000 in immunodeficient population. This disorder is frequently unidentified in early phase of the disease due to its unspecific symptoms and signs.1 This joint infection can cause numerous problems to the patient ranging from joint damage, bone erosion, osteomyelitis, fibrosis, ankylosis, sepsis,or even death.1-5 The case-fatality rate for this disorder can reach up to 11%, comparable to the case fatality rate for other community infections such as pneumonia.2,6 Salmonella sp. is a Gram-negative bacillus bacterium with main invasion predilection in intestinal villi.7 This microorganism rarely causes septic arthritis although several cases have been reported before. Ortiz-Neu et al. demonstrated that septic arthritis caused by Salmonella sp. has high relapse incidence and a tendency to turnchronic, making the treatment more difficult and challenging